Typical Drinking, Sensation Seeking, and Alcohol Expectancies Regarding Sexual Coercion as Predictors of Coercive Condom Use Resistance Perpetration - Kirwan, Mitchell (Journal of interpersonal violence, 2023)
Although condoms are effective at preventing sexually transmitted infections (STIs) and unwanted pregnancies, condom use resistance (CUR) remains prominent. In particular, coercive CUR, or the use of coercive tactics to resist condom use with a partner who wants to use one, comprises a unique combination of sexual aggression and risky sexual behaviors, making it especially problematic. The present study sought to examine the relationship between coercive CUR and a variety of factors associated with both sexual aggression and risky sexual behaviors (e.g., typical alcohol consumption, alcohol expectancies regarding sexual aggression, and sensation seeking) to determine whether such factors may also contribute to the etiology of coercive CUR. To do so, a nationwide study of 102 young, heterosexual men who had previously perpetrated coercive CUR were recruited to complete an online, cross-sectional survey. Data were analyzed using a hierarchical linear regression model, which showed that alcohol expectancies regarding sexual coercion and sensation seeking moderated the relationship between typical drinking quantity and previous coercive CUR perpetration, such that typical drinking was positively associated with coercive CUR among men who reported greater sensation seeking and alcohol expectancies regarding sexual coercion. However, among men who were low in one or both of these factors, typical drinking was not associated with coercive CUR. These results suggest that typical drinking, alcohol expectancies, and sensation seeking may all be important to the etiology of coercive CUR, and that a reduction in one or more may be sufficient to reduce the likelihood of coercive CUR perpetration. Future research should confirm these findings using experimental and/or longitudinal methodologies and seek to develop intervention programs targeting typical alcohol use, alcohol expectancies related to sexual coercion, and sensation seeking in young men.